Pelatihan Pembuatan Pempek untuk Meningkatkan Keterampilan dan Penggerak Ekonomi Berbasis Masyarakat - Terttiaavini Terttiaavini; Tedy Setiawan Saputra; Lesfandra Lesfandra; Fauziah Afriyani (I-Com: Indonesian Community Journal, 2024)
This pempek-making training was organised as an effort to improve skills and encourage community-based economic growth in Palembang City. The problems faced are the limited knowledge and skills of the community in producing quality pempek and the lack of opportunities to develop micro businesses in the culinary field. The purpose of this training is to provide training and support to women in Palembang City who are interested in starting various pempek making business, so as to open new business opportunities, create jobs, and increase income and economic welfare. The training involved collaboration with the Palembang City Trade Office. The results of the training showed that participants were satisfied with the training materials, instructors, facilities, training process and training outcomes. However, there was dissatisfaction with the economic impact that has not been felt by the participants. This training requires further evaluation and improvement strategies to have a more significant impact